Genotyping by sequencing; a strategy for identification and mapping of induced mutation in newly developed wheat mutant lines - Sana Zulfiqar; Mehboob-ur- Rahman; Sayyad Ali Raza Bukhari; Till, Bradley; Ruixue Gu; Dongcheng Liu; Dreisigacker, Susanne (Springer, 2024)
Exposing genetic material with physical mutagens can create novel genetic resources capable of combating different stresses. High throughput GBS-DArTseq (TM) assay was deployed to estimate genetic diversity of 33 newly developed stable wheat mutants as compared to the wild type. The identified 1,57,608 PAVs markers were randomly distributed across wheat chromosomes and sub-genomes with the highest number detected on Chr-7D (2877) and Chr-7B (2711). The B sub-genome contained the most PAVs followed by D and A-sub genome. Among mutant lines, Pb-M-2061 and Pb-M-59 had the highest PAV count, while Pb-M-605 and Pb-M-196 had the lowest. A total of 7,910 PAVs were consistently present over all replicates, with 3,252 specifically present in mutants and absent in wild type. The maximum PAVs (1480) were found in Pb-M-1027 and Pb-M-1323 (656). Functional characterization revealed that out of 3,252, 1,238 were found in wheat transcriptome database that contained 152 characterized and 1,196 uncharacterized genes. COGs and GO-terms analysis linked many PAVs with pathways involving signaling, metabolism and defense. Maximum number of gene-containing PAVs were identified in Pb-M-1027, Pb-M-2302 and Pb-M-1323 which were involved in tolerance to diseases and abiotic stresses, improved photosynthetic efficiency, larger grain size, increased grain yield and harvest index pathways. This study provides valuable insights into the genetic diversity and potential agronomic benefits of PAVs in wheat mutant lines. These findings can help molecular geneticist and breeders for exploiting the induced genetic diversity for unravelling the genetic circuits as well as exploiting in wheat breeding for developing resilient cultivars.